2020
DOI: 10.1038/s41598-020-64043-y
|View full text |Cite|
|
Sign up to set email alerts
|

Revealing the air pollution burden associated with internal Migration in Peru

Abstract: This study aims to quantify changes in outdoor (ambient) air pollution exposure from different migration patterns within Peru and quantify its effect on premature mortality. Data on ambient fine particulate matter (PM 2.5) was obtained from the National Aeronautics and Space Administration (NASA). Census data was used to calculate rates of within-country migration at the district level. We calculated differences in PM 2.5 exposure between "current" (2016-2017) and "origin" (2012) districts for each migration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 88 publications
0
1
1
Order By: Relevance
“…It has recently been suggested that pollution may play a role in stunting [53] and previous research in Peru found that migrants in Greater Lima had a 10-fold increase in exposure to larger particulate matter (PM2.5) compared to non-migrants [54]. We did not find higher levels of stunting in children of migrants compared to nonmigrants in larger cities but further investigation should compare child growth in areas with different levels of pollution within cities and at different ages.…”
Section: Potential Mechanismscontrasting
confidence: 75%
“…It has recently been suggested that pollution may play a role in stunting [53] and previous research in Peru found that migrants in Greater Lima had a 10-fold increase in exposure to larger particulate matter (PM2.5) compared to non-migrants [54]. We did not find higher levels of stunting in children of migrants compared to nonmigrants in larger cities but further investigation should compare child growth in areas with different levels of pollution within cities and at different ages.…”
Section: Potential Mechanismscontrasting
confidence: 75%
“…In contrast, established migration networks may increase an individual's propensity to move. Second, either through lack of information about risks at destinations or as the outcome of a balancing of risks, migrants might move to areas that are more or less exposed to climate change impacts than those where they came from (8,9). Third, climate change is likely to lead to resource depletion in some of the most deprived areas, thereby trapping individuals who cannot afford to move (10,11).…”
mentioning
confidence: 99%